If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + 16 = 7m + 12 Reorder the terms: 16 + 6m = 7m + 12 Reorder the terms: 16 + 6m = 12 + 7m Solving 16 + 6m = 12 + 7m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-7m' to each side of the equation. 16 + 6m + -7m = 12 + 7m + -7m Combine like terms: 6m + -7m = -1m 16 + -1m = 12 + 7m + -7m Combine like terms: 7m + -7m = 0 16 + -1m = 12 + 0 16 + -1m = 12 Add '-16' to each side of the equation. 16 + -16 + -1m = 12 + -16 Combine like terms: 16 + -16 = 0 0 + -1m = 12 + -16 -1m = 12 + -16 Combine like terms: 12 + -16 = -4 -1m = -4 Divide each side by '-1'. m = 4 Simplifying m = 4
| 0.3x+0.8(20-x)=0.1(10) | | -57+4x=15 | | 2y+5(y-4)=3x+2 | | Log(x+2)1000=3 | | 6+7r=6+7r | | a^2-30a+225=0 | | 3x^3=y | | (5-6i)-(-8+2i)=0 | | 7n-2n=1+6n-7+8 | | 2t^2=25t+13 | | 5b-6-8b-8= | | 4a-2=6a-3a+6 | | 5+8x-3-2=4x+5x | | 10x-96=114+3x | | ax+9=7x+b | | 9x+5y= -60 | | 30y+2=14 | | 11-4r=-3(r-5) | | 3+r=6+6r-2r | | -49-2x=-6x+31 | | 6(12x+8)=72x-3 | | 6x+4x-28=42-4x | | r=-6r-7r | | 0.1x=2forx | | 10-3x=3-5x+x | | 7h-28=28 | | p+3-7=3+7p-2p-7 | | 5x-w=vx+y | | (3x^2)-3x-4=0 | | -3(x+3)+6=7(x+5)+6 | | 2y^2=128 | | -4x+5y+16=0 |